Nature of events and alcohol-related content in marketing materials at a university freshers’ fair: a summative content analysis - Fuller, Amy; Fleming, Kate M.; Szatkowski, Lisa; Bains, Manpreet (Oxford University Press, 2017)
Introduction:The transition to university is a potentially influential time upon students’ drinking behaviour. This study explored the nature of activities and alcohol-related content in marketing materials from student-led societies and local businesses provided to students, at a university freshers’ fair in the UK.